THE THEATRE AND THE CAMERA. ON CINEMATIC MEETINGS WITH THE THEATRE OF LESZEK MĄDZIK - Ziółkowska-Kurczuk, Natasza (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article deals with the problem of filmmaking of the theatrical performances created by the Artistic Stage of KUL. On the other hand, concerns the issue of the film recording of Leszek Mądzik's stage works. The authoress writes about it from the perspective of a film director and as a researcher analyzing visual arts. It refers to psychological and post-structural film theories, especially in french science. In the article can be also find personal reflections on the film recordings of theatrical work. The authoress tries to give an answer to how the presence of the camera transforms the performances.